Implementation of Profit and Loss Sharing in Rubber Plantation Parcels from the Perspective of Sharia Economic Law - Adam Hafidz Al Fajar; Willy Maulana; Bima Fandi Asy’arie (PT. Islamic Research Publisher, 2024)
This research aims to describe the practice of a rubber plantation sharing agreement between a rubber plantation owner and a cultivator in Mekar Jaya Village, Banjar Margo Sub-district, Tulang Bawang Regency. This agreement is oral and, unfortunately, does not always go as expected, facing some significant problems. Cultivators proved to be irresponsible in their work, sometimes working and sometimes not. The imbalance of this agreement is detrimental to the owner of the rubber plantation, violating the principles of the Musaqah contract, which should include timely labour. The formulation of the research problem includes aspects of the practice of profit and loss sharing in rubber plantation parcels in Mekar Jaya Village, as well as the perspective of sharia economic law regarding this agreement between cultivators and plantation owners. This research aims to understand the practice of profit and loss sharing in rubber plantation parcels in Mekar Jaya Village and analyse it from the perspective of sharia economic law. The research method used is qualitative with the type of field research that is descriptive analysis. The results show that the practice of rubber profit-sharing agreements in Mekar Jaya Village is in accordance with the pillars and conditions of Musaqah in Islam, but not entirely in accordance. The clear agreement and fulfilment of the pillars and conditions of Musaqah make the agreement valid according to Islamic law. However, some discrepancies with the principles of Musaqah caused some of the parties to not fulfil the terms and conditions of Musaqah.